The Medial Femoral Condyle Flap: A Novel Versatile Tool for Complex Microvascular Maxillofacial Reconstruction. Issue 1 (18th October 2022) - Ismail, Tarek; Kurlander, David E.; Lee, Z-Hye; Lunger, Alexander; Shuck, John W.; Largo, Rene D.; Chang, Edward I.
Abstract : Summary: The medial femoral condyle flap is well-described for reconstruction of small bone defects of the upper and lower extremities. There are limited case reports of its use in other anatomic sites, particularly for reconstruction of complex head and neck defects. In the setting of previous radiation and contaminated fields, vascularized bone is generally preferred to bone grafts, cadaveric allografts, or synthetic implants. The authors present a case series of complex craniofacial defects involving the midface that were reconstructed using medial femoral condyle flaps, focusing on the type of defect and lessons learned from their early experience to promote awareness of this flap among microsurgeons, who may wish to consider the potential of this flap and incorporate its use into their armamentarium. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.